(3eQGcR GdGSJbQGQ ai eUQ GdYdjG ai bGehS eMeO QeRi h JMbjbgG LZQGajG ai GdYUQ GdhSjW ef (B20(3g` `(B-922(3g`(B/640(3e(B-1517(3e(B: s (3OQGSI ai GdLZQGajG GdJGQjNjI HGSJNOGe fXe GdeYdheGJ GdLZQGajI (B/ s - (3jGSejf eMeO eMeO GdMSjfis; (3LjgGf eUWai GdHjhei (B: s; (3SjO YHOGdNGdb GdSjO YQaGf (B: s ((3GdbGgQI (B: s (3jGSejf eMeO eMeO GdMSjfi (B: s, 2020)
(3JJCda GdOQGSI ef SJ aUhd(B: (3JSHbgG ebOeI h JTJed Ydi JegjO dehVhY GdOQGSI(B: (3ehbY GdOQGSI h MOhOgG(B: (3CSHGH GNJjGQ GdehVhY(B: (3CgOGa GdOQGSI(B: (3efgL GdOQGSI(B: (3GdUYhHGJ GdJi hGLgJ GdWGdHI(B: (3Ke Cge GdOQGSGJ GdSGHbI(B: (3h CNjQkG efgL h NWI GdOQGSI(B: (3h JJHYgG NGJeI(B: (3bGFeI HGdeUGOQ h GdeQGLY(B: (3h LGAJ eMJhjGJ GdOQGSI Ydi GdfMh GdJGdi(B: (3jJfGhd GdaUd GdChd(B: ((3GdLZQGajG GdWHjYjI deUQ GdYdjG(B) (3ef NdGd OQGSI GdEWGQ GdecGfi GdNQjWI GdcfJhQjI h GdCTcGd GdCQVjI h GdefGN h GdSgd GdajVi h GdJQHI(B. (3h jOQS GdaUd GdKGfi(B: ((3GdLZQGajG GdGLJeGYjI deUQ GdYdjG(B) (3ef NdGd GdCUhd GdYQjbI ddScGf(B: (3h GdLhGfH GdLZQGajI h GdGLJeGYjI dScGf eUQ GdYdjG(B. (3h jJfGhd GdaUd GdKGdK(B: ((3GdYeQGf ai eUQ GdYdjG(B) (3ef NdGd OQGSI YOO GdbQi h MLe GdbQi h ehGVY GdbQi h CfhGYgG h CSeGA GdbQi HGdEVGaI Edi JhGHYgG h GdbQi GdMGOKI h CNjQkG XGgQI GfOKGQ GdbQi h CNjQG YQV dOQGSI WQb Gdfbd h GdehGUdGJ ai eUQ GdYdjG h Cge gPg WQb cGfJ fgQjI Ch HQjI Ch HQjOjI Ch CHQGL GdMeGe GdHWGFbi(B. (3h jJfGhd GdaUd GdQGHY(B: ((3eQGcR GdGSJbQGQ GdHTQi ai GdUYjO GdCYdi(B) (3ef NdGd OQGSI GdCYeGd GdbhUjI h GdCNejejI h cd eG jNU GdCYeGd ef edGeM GdYGeI ddEWGQ GdecGfi h GdMUQ GdYGe ddbQi h GdfhGMi ai GdYUQ GdhSjW h GdLOGQI GdEfJGLjI ddCQGVi GdRQGYjI(B: (3h HYV GdeSejGJ h GdCdaGX GdYeQGfjI h CMLGe GdbQi h CNjQkG GdJhRjY GdLZQGai ddbQi ai VhA GdCbSGe GdEOGQjI GdMGdjI(B. (3h jOQS GdaUd GdNGeS(B: ((3eQGcR GdGSJbQGQ GdHTQi ai GdUYjO GdChSW(B) (3ef NdGd OQGSI GdCYeGd GdCSjhWjI h GdefadhWjI h GdCTehfjjf h cd eG jNU GdCYeGd ef edGeM GdYGeI ddEWGQ GdecGfi h GdMUQ GdYGe ddbQi h GdfhGMi ai GdYUQ GdhSjW h GdLOGQI GdEfJGLjI ddCQGVi GdRQGYjI(B: (3h HYV GdeSejGJ h GdCdaGX GdYeQGfjI h CMLGe GdbQi h CNjQkG GdJhRjY GdLZQGai ddbQi ai VhA GdCbSGe GdEOGQjI GdMGdjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI MdhGf (B- (3cdjI GdBOGH (B- (3bSe GdLZQGajGs
(3UOQ GjVG cbQU eOeLs